Designing sustainable polymers: lactate esters for 3D printing and upcycling [data] - Klee, Pia S.; Vázquez-Martel, Clara; Flórido Martins, Lilliana; Blasco, Eva (Universität, 2023)
The search for sustainable polymer systems is key to tackling the current climate crisis. However, the use of bio-based polymers does not suffice to achieve this goal. Additionally, new chemical approaches enabling the re- or upcycling of polymer materials need to be explored. Herein, we exploit lactate esters with different substituents as readily available bio-based molecules for the synthesis of printable monomers. The synthesis of these lactate ester-based monomers follows green chemistry principles by establishing a solvent-free, one-pot approach, relying on a reusable catalyst, and achieving high conversions (84 - 100%) at mild conditions. Further, these monomers are utilized in 3D printable ink formulations for digital light processing (DLP) for the first time in combination with a recycled crosslinker. The resulting 3D printed structures display complex geometries with high resolution. A key attribute of the presented system is that the 3D printed polymer material can be upcycled via aminolysis affording a pre-cursor of the crosslinker, which is in turn incorporated into the further ink formulations, introducing a material circularity into the system. These results demonstrate a powerful approach by combining bio-based monomers and chemical upcycling with sustainable 3D printing techniques.
Gesehen am 22.11.2023
Keywords: Forschungsdaten; Datenbank